Baseline survey on mixed farming systems in Bangladesh: Manual for survey data collection - Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2024)
This manual will guide enumerators participating in the SI-MFS Baseline Survey, Bangladesh as they engage in data collection activities in households. The following sections are included: -Background of the study -Sampling strategy -Note on first-time visits to households -Roles and responsibilities of the enumerators -General instructions for data collection -Detailed questionnaire guideline